Wstrętny świat Michela Houellebecqa - Bronikowska, Aleksandra (Wydawnictwo Wydziału Nauk Społecznych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
Michel Houellebecq – provocator and scandalist is in fact conservative. The elementary particles and The possibility of an Island show man’s helplessness towards postcapitalism, the fall of masculation and his yearning for tradition. Abhorrent is not perverse sex described on novels, but human powerlessness. Author shows his own eroticosophy to chart the changes of society after sexual revolution. His diagnosis of human condition is drab.
Keywords: miłość postmodernizmu; seksualność; wstręt; męskość; Michel Houellebecq